Importância da propriedade intelectual na concepção marcaria : uma análise do cenário do registro de marca nas indústrias sergipanas - Nascimento, Rosa Leila Lima do (2016)
Intellectual property is an instrument that gives the author the protection of their legal rights involving essential factors in property protection requirement or exclusivity resulting from intellectual activity in the industrial, scientific, literary and artistic. The brand is characterized as an element of intellectual property, since the registration of a trademark and its dissemination in the industrial scenario can become synonymous with reliability when it becomes identified as a benchmark for quality, durability of strength, status, and security for the customer's product or service. Therefore, this study aimed to verify the benefits for small and medium-sized companies that decide to register your trademark, specifically in the design of the registration of marks in Sergipe industries. For field research were used the information obtained in the questionnaires used in the industries of manufacturing segments, wood and furniture, information technology, metalworking, food, chemicals, ceramics, oil and gas and others, seeking to identify the importance attached for them to brand management. It was noted that there is a lot of resistance by entrepreneurs register their brands, especially the little knowledge about the importance of registration and the bureaucratic system involving the legal formalities.